Crohn's disease involving the penis. Issue 3 (March 1986) - Slaney, G; Muller, S; Clay, J; Sumathipala, A H; Hillenbrand, P; Thompson, H
Abstract : Perianal complications of Crohn's disease occur in 25-70% of patients but perineal and genital lesions are rare. Treatment is controversial and there is a risk of recurrent or persistent disease. We report two cases of Crohn's disease involving the penis, one with multiple scrotal urinary fistulae, partial destruction of the proximal urethra, and ulceration of the penile shaft; the other with metastatic cutaneous ulceration of the penile shaft. The second case is particularly unusual in that the patient presented at the VD clinic as a case of syphilis.